Β-1, 3-d-Glucan based yeast cell wall system loaded emodin with dual-targeting layers for ulcerative colitis treatment. (1st December 2021) - Pu, Xiulan; Ye, Naijing; Lin, Meisi; Chen, Qiyan; Dong, Lingling; Xu, Haiting; Luo, Ruifeng; Han, Xiaoqin; Qi, Shanshan; Nie, Wenbiao; He, Haoqi; Wang, Yanli; et al.
Abstract: Herein, a β-1, 3-d -glucan based microcarrier, yeast cell wall microparticles (YPs), was used to develop a food-source-based nano-in-micro oral delivery system for ulcerative colitis (UC) treatment. Briefly, lactoferrin (Lf), which targets intestinal epithelial cells, was used to encapsulate emodin (EMO) to form nanoparticles (EMO-NPs), and then loaded into YPs with the natural macrophages targeting ability, forming a final formula with two outer–inner targeting layers (EMO-NYPs). These dual-targeting strategy could enhance the dual-effects of EMO in anti-inflammatory and mucosal repair effects respectively. As expected, cell uptake assessment confirmed that EMO-NPs and EMO-NYPs could target on the Lf and dection-1 receptors on the membranes of Caco-2 cells and macrophages, respectively. Importantly, EMO-NYPs showed the best anti-UC effects compared to EMO-NPs and free EMO, by inhibiting NF-κB pathway to anti-inflammation and promoting intestinal mucosa repair via MLCK/pMLC2 pathway. The results show that EMO-NYPs are a promising food-based oral delivery system in anti-UC. Highlights: A yeast cell wall based oral delivery system with dual-targeting layers was developed. Dual-targeting layers target intestinal epithelial cell and macrophages, respectively. EMO-NYPs could be anti-UC by anti-inflammation and promote intestinal mucosa repair. EMO can play a role in intestinal mucosa repair via the MLC2 signaling pathway